Panorama del diseño industrial en la región - Olarte, Jorge Alberto (Universidad de San Buenaventura - Cali, 2017)
Through the historical analysis of the development of the concept of industrial design, was addressed the study in Latin America, especially where his academic interest in its beginning in countries like Mexico, Argentina, Brazil and in Colombia between the 70’s with some architects pioneers who contributed to the creation of schools in these countries. Some studies in Latin America become promoters of industrial design, leading processes of industrialization in close relationship between academy and private companies. The article is particularly interested in the comparative statement in the academic programs of three universities in the region of Valle del Cauca in Colombia; University of Valle, National University of Palmira, University Icesi of Cali, shared design programs seeking the academic relationship with private company with a sense of social responsibility and business as the environment. Emphasis is in on the Icesi University whose student profile seeks to create concerns the organization of the company with social consciousness and responsibility as well as the commitment of enterprise development, student facing a reality of the entrepreneurs on the ignorance of their work and the importance of industrial development of companies; students who ends underemployed as users of software underpaid.